2020
DOI: 10.3390/app10175800
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phase Noise in a Hybrid Photonic/Millimetre-Wave System for Single and Multi-Carrier Radio Applications

Abstract: The future evolution of wireless networks, throughout the 5G era and beyond, will require the expansion and augmentation of millimetre-wave systems for both terrestrial and satellite communications. Photonic technologies offer a cost efficient and high bandwidth platform for millimetre-wave carrier generation and distribution, but can introduce high levels of phase noise through optical heterodyning, which is highly problematic for mobile signal waveforms. In this work, a detailed analytical model of a hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The composite mmwave signal (carrier and data signal are amplified and then transmitted over a wireless link of 1 -2 m using a set of 20 dB gain directional horn antennae. The transmission of the mm-wave data signal alongside a phase noise correlated carrier, enables phase noise and frequency offset cancellation using an analog electrical PNC receiver structure which is described in detail in [5,17] . Mixing of the mm-wave carrier and data sideband terms at the PNC stage produces a clean IF OFDM signal which is then captured by a real time oscilloscope (RTO) at 50 GSa/s before offline processing consisting of synchronization, channel estimation and equalisation and EVM measurement was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite mmwave signal (carrier and data signal are amplified and then transmitted over a wireless link of 1 -2 m using a set of 20 dB gain directional horn antennae. The transmission of the mm-wave data signal alongside a phase noise correlated carrier, enables phase noise and frequency offset cancellation using an analog electrical PNC receiver structure which is described in detail in [5,17] . Mixing of the mm-wave carrier and data sideband terms at the PNC stage produces a clean IF OFDM signal which is then captured by a real time oscilloscope (RTO) at 50 GSa/s before offline processing consisting of synchronization, channel estimation and equalisation and EVM measurement was performed.…”
Section: Methodsmentioning
confidence: 99%
“…optical access networks) for mm-wave generation and distribution -a concept known as 'convergence' [2,3] . Indeed, our previous works have explored how a pair of optical carriers with a mm-wave frequency difference may be distributed over an analog radio-over-fiber (A-RoF) fronthaul link from a central office (CO) to a remote radio head (RRH) for heterodyne detection; directly producing a mm-wave mobile signal after the photo-detection stage [4,5] . Although the A-RoF (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…1 -provides reduced cost and complexity of RUs at the antenna sites [20], [26], helping to facilitate network scaling. The authors' recent works have demonstrated how this RAN architecture can be deployed in conjunction with centralized, flexible optical heterodyne mm-wave generation and A-RoF transmission; serving to increase system spectral efficiency and flexibility while further reducing RU complexity [5], [6]. These aspects are particularly advantageous for future C-RAN deployments considering the ultra-dense deployment of the antenna sites required for high-frequency wireless systems [7].…”
Section: Convergence Of Optical and Wireless Networkmentioning
confidence: 99%
“…More recently, research has focused on how these methods may be integrated with existing optical infrastructure (e.g., optical access networks) for mm-wave generation and distribution -a concept known as 'convergence' [3], [4]. Indeed, our previous works have explored how a pair of optical carriers with a mm-wave frequency difference may be distributed over an A-RoF fronthaul link from a central office (CO) consisting of a central unit (CU) and distributed unit (DU) to a remote radio unit (RU) for heterodyne detection; directly producing a mm-wave mobile signal after the photo-detection stage [5], [6]. Although the A-RoF transmission approach introduces stringent linearity, phase noise and frequency offset requirements [5], it holds a distinct advantage over current digital approaches in terms of both spectral efficiency and the potential for network scaling [7].…”
mentioning
confidence: 99%
“…In the latter, OFDM properties are combined with numerical algorithms to recover data even with high carrier phase noise. By mitigating the impact of optical coherence these algorithms are a path to relax the constraints on sources purity [28], allowing a widespread use of cheap and common laser sources in OFDM mm-wave transmissions. In particular this can be used to make OPLLs a better candidate for the generation of remote-fed optical LOs and it represents a very promising and viable method for the new 5G ARoF fronthaul.…”
Section: Introductionmentioning
confidence: 99%